1999
DOI: 10.1088/0022-3727/32/10/311
|View full text |Cite
|
Sign up to set email alerts
|

A self-consistent numerical analysis of a planar dc magnetron discharge by the particle-in-cell/Monte Carlo method

Abstract: The structure of axisymmetrical dc planar magnetron discharge is clarified by the use of the particle-in-cell/Monte Carlo method. The magnetron has two concentric cylindrical magnets behind the cathode. Here the effects of magnetization in the magnets, M, and the emission coefficient of secondary electrons, γ , on the discharge structure are examined. Four discharge conditions are considered: (i) M = 0.50 T and γ = 0.12, (ii) M = 0.75 T and γ = 0.12, (iii) M = 1.00 T, γ = 0.12 and (iv) M = 0.50 T and γ = 0.15.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
48
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(53 citation statements)
references
References 26 publications
5
48
0
Order By: Relevance
“…2.4, the value of β increases with increasing γ i . As discussed in [56] this is because, for a fixed discharge voltage, a higher γ i produces a higher plasma density [52], which means a lower plasma impedance and, therefore, a higher value of β.…”
Section: Effect Of Electron Recapture At the Cathodementioning
confidence: 93%
See 1 more Smart Citation
“…2.4, the value of β increases with increasing γ i . As discussed in [56] this is because, for a fixed discharge voltage, a higher γ i produces a higher plasma density [52], which means a lower plasma impedance and, therefore, a higher value of β.…”
Section: Effect Of Electron Recapture At the Cathodementioning
confidence: 93%
“…As an example, Kondo and Nanbu [52] found with a Monte Carlo model a substantial decrease in both the electron density and ionization rate when decreasing γ from 0.15 to 0.12. Shidoji et al [53] discussed the influence of the electron yield on the current-voltage characteristic of the Ar discharge using a hybrid model, with γ = 0.0005 V a , where V a is the applied voltage (in the range 240-400 V).…”
Section: The Role Of Ion-induced Electron Emission In Glow Dischargesmentioning
confidence: 99%
“…Since the motions of charged particles near the cathode is complicated by the complex configurations of magnetic and electric fields, many efforts have been made to accurately understand the discharge phenomena near the cathode through experimental [5][6][7][8][9][10][11][12] and theoretical works. [13][14][15][16][17][18][19] In theoretical works, two approaches of fluid model [13][14][15] and particle-in-cell/Monte Carlo method [16][17][18][19] have performed but, the PIC/MC simulations have been preferably done in spite of heavy computational load because of the inadequacy of the fluid model in lowpressure discharges of few mTorr and then, have provided a lot of information. However, the fluid model is in itself of great value in supplying the perspective understanding about the effects of various discharge parameters.…”
Section: Introductionmentioning
confidence: 99%
“…13 van der Straaten et al performed a one-dimensional PIC/MC simulation of a cylindrical postcathode magnetron and found that the discharge exhibits a transition from the positive-space-charge mode at higher pressure to the negative-space-charge mode at lower pressure. 16,17 Kondo and Nanbu recently developed a self-consistent three-dimensional PIC/MC simulation 18,19 and examined the effects of the magnetic field and the secondary electron emission on the discharge structure. 19 Most of authors treated the mobility and diffusion dominated electron transport and the structure of plasma potential was determined for the balance of the discharge current, i.e., the balance between ion loss in the cathode and electron loss in the anode.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation